1975
DOI: 10.1104/pp.55.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alfalfa Stem Conductance Induced by Corynebacterium insidiosum Toxin

Abstract: A toxin involved in bacterial wilt of alfalfa (Medicago sativa L.) has been isolated from cultures of the pathogen, Corynebacterium insidiosum, as well as from diseased plants (S. M. . Physiological Plant Pathology 2: 133-142). The influence of this toxin, a glycopeptide with a molecular weight of 5 X 106, on the water relations of alfalfa was examined. It was found that very small amounts of the toxin (2 Ag) significantly reduced stem conductance through 15-cm long stems. This decrease in stem conductance cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Other workers have not detected any physiological (175) or ultrastructural (184) evidence of membrane damage in either alfalfa cuttings treated with low concentrations of C. m. ssp. insidiosum "toxin" (175) or in infected alfalfa plants (37) or infected tomato plants (184). In the Van Alfen & Turner (175) study, as little as 2 p.g of toxin forced into the stem resulted in a marked (19%) decrease in water conductance, and 200 p.g/ml was effective in visible wilting.…”
Section: Pathogenicity Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Other workers have not detected any physiological (175) or ultrastructural (184) evidence of membrane damage in either alfalfa cuttings treated with low concentrations of C. m. ssp. insidiosum "toxin" (175) or in infected alfalfa plants (37) or infected tomato plants (184). In the Van Alfen & Turner (175) study, as little as 2 p.g of toxin forced into the stem resulted in a marked (19%) decrease in water conductance, and 200 p.g/ml was effective in visible wilting.…”
Section: Pathogenicity Factorsmentioning
confidence: 95%
“…sepedonicum "toxin" per ml for 2 hr and for potato stems sampled 4 to 5 weeks after inoculation with the same organism (71). Other workers have not detected any physiological (175) or ultrastructural (184) evidence of membrane damage in either alfalfa cuttings treated with low concentrations of C. m. ssp. insidiosum "toxin" (175) or in infected alfalfa plants (37) or infected tomato plants (184).…”
Section: Pathogenicity Factorsmentioning
confidence: 95%
“…Van Alfen and Turner showed that two of these large phytotoxins, produced respectively by Corynebacterium insidiosum (8) and Ceratocystis ulmi (9), act by interfering with water conduction in the plant's vascular system and not by any direct toxicity to plant cells. The decrease in vascular conductance through stems of the wilted cuttings caused by these macromolecules was not large.…”
mentioning
confidence: 99%
“…In most of the work reported by other authors, purified bacterial polysaccharides (see Corey & Starr 1957) or artificially synthesized polymers were applied to elucidate the mechanisms of phytopathogenicity. The effects of polysaccharides on ornamental cut flowers, however, have rarely been studied (Hodgson et al 1949;Van Alfen & Turner 1975;Van Alfen & Allard-Turner 1979;Van Alfen et al 1983;de Stigter & Broekhuysen 1986;Neumann 1987). In the present work, molecular filtrates and retentates of supernatant fluids of pure cultures of several micro-organisms grown in an agitated sucrose-containing medium were used as a vase medium for cut roses cv.…”
mentioning
confidence: 87%
“…Thus, in addition to diverting xylem flow, xylem-borne polymers might directly induce senescence of leaf cells (Neumann 1987). The apparent absence of visible xylem blockage by plant polysaccharides reported by Van Alphen &Turner (1975) andNeumann (1987) suggests that complex hormonal regulation may affect polysaccharide concentrations in specific sections of the xylem system. To reveal the occurrence of this phenomenon, further research is needed (Halverson & Stacey 1986).…”
Section: Effects Of T H E I N F I L T R a T I O N Of M I C R O B I A mentioning
confidence: 98%